PEMBUATAN PEPTON DARI BUNGKIL KEDELAI DAN KHAMIR DENGAN ENZIM PAPAIN UNTUK MEDIA PERTUMBUHAN BAKTERI [Peptone Production From Soybean Press Cake and Yeast By Papain Enzyme For The Bacterial Growth Media] - . Fachraniah; Dedi Fardiaz; Tami Idiyanti (Jurnal Teknologi dan Industri Pangan, 2002)
Peptone can be produced from soybean press cake and yeast by enzymatic hydrolysis with papain. The activity of papain used in this experiment against casein is indicated by Vm (2000 unit) and Km (0.8%). The process condition for soybean press cake was : [S] = 3.72%, [E] = 0.4%, 60 0C, pH 6.2-6.3, 5 hours, while for yeast was [S] = 4.76%, [E] = 0.2%, 60 0C, pH 5.8-5.9, 5 hours. The yield of the hydrolysis process of soybean press cake peptone was 12.1%, while that of yeast was 18.9%. The peptone obtained was brownish yellow in color with moisture content of 3 and 5%, ash content 6 and 7 %, total protein 9 and 11%, solubility 98%, amino nitrogen 1.9 and 2.82, and AN/TN ratio = 26.47 and 27.62%, respectively. The chromatographic pattern of the peptone using gel filtration column of Superdex-75 appeared to be the same as that of the commercial soy pepton. Growth test with E. coli, S. aureus, and B. subtilis showed that soybean press cake and yeast peptone could be used as component in media for microbial growth.